Does Immigration Improve Quality of Care in Nursing Homes? - Delia Furtado; Francesc Ortega (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2022)
This paper explores how immigrants may address nursing home staffing shortages that are likely to worsen as baby boomers age. We show that more immigrant labor leads to fewer falls, less usage of restraints, and fewer pressure ulcers among nursing home residents, as well as improvements in other measures of quality of care. Consistent with a labor market explanation, we find that immigration increases the local supply of nurse assistants - the workers responsible for hands-on care in nursing homes. Additionally, we find evidence of crowding-in of natives into the nursing assistant occupation, consistent with lower-skilled immigrants displacing natives away from informal employment in household services. Finally, we show that that immigration leads to better nursing home care quality only in competitive nursing home markets.
Keywords: 330